The Song of Songs from the Bible to the Mishnah - Kaplan, Jonathan (Hebrew Union College annual, 2013)
Beginning in the second and third centuries C.E., both Christian and rabbinic literature evince a flowering of interpretation of Song of Songs. Evidence for sustained interpretation of Song of Songs before the second century C.E. is, however, scant. The aim of this article is to address the historical question of when we can detect the emergence of interpretation of Song of Songs in extant literature before the advent of a formal commentary on Song of Songs in both Judaism and Christianity in the third century C.E. This article suggests that the date for the first interpretations of Song of Songs can now be firmly pushed back from the beginning of the second century C.E. to the close of the first century C.E. Employing recent methodological work in biblical studies on intertextuality and literary allusions and echoes, I argue that the interpretation of Song of Songs as a divine love song appears first in extant Jewish literature after the destruction of the Second Temple in 4 Ezra and Revelation. Both 4 Ezra and Revelation strongly emphasize the role of the male character of Song of Songs in bringing redemption. Both texts look forward to a final eschatological victory for God and the faithful, portrayed in part with language drawn from Song of Songs. Song of Songs, read apocalyptically and as a divine love song, is one of many literary referents used to reassure their readers of God's fidelity and love.